Modeled Effect of Coastal Biogeochemical Processes, Climate Variability, and Ocean Acidification on Aragonite Saturation State in the Bering Sea - Pilcher, Darren J.; Naiman, Danielle M.; Cross, Jessica N.; Hermann, Albert J.; Siedlecki, Samantha A.; Gibson, Georgina A.; Mathis, Jeremy T. (Frontiers in Marine Science, 2019)
The Bering Sea is highly vulnerable to ocean acidification (OA) due to naturally cold, poorly buffered waters and ocean mixing processes. Harsh weather conditions within this rapidly changing, geographically remote environment have limited the quantity of carbon chemistry data, thereby hampering efforts to understand underlying spatial-temporal variability and detect long-term trends. We add carbonate chemistry to a regional biogeochemical model of the Bering Sea to explore the underlying mechanisms driving carbon dynamics over a decadal hindcast (2003-2012). The results illustrate that coastal processes generate considerable spatial variability in the biogeochemistry and vulnerability of Bering Sea shelf water to OA. Substantial seasonal biological productivity maintains high supersaturation of aragonite on the outer shelf, whereas riverine freshwater runoff loaded with allochthonous carbon decreases aragonite saturation states (ΩArag) to values below 1 on the inner shelf. Over the entire 2003-2012 model hindcast, annual surface ΩArag decreases by 0.025 – 0.04 units/year due to positive trends in the partial pressure of carbon dioxide (pCO2) in surface waters and dissolved inorganic carbon (DIC). Variability in this trend is driven by an increase in fall phytoplankton productivity and shelf carbon uptake, occurring during a transition from a relatively warm (2003-2005) to cold (2010-2012) temperature regime. Our results illustrate how local biogeochemical processes and climate variability can modify projected rates of OA within a coastal shelf system.